Visual search for motion-form conjunctions: selective attention to movement direction. - Mühlenen, Adrian von; Müller, Hermann J. (Journal of General Psychology, 1999)
Part of a special issue on visual attention. Two experiments were conducted to investigate whether motion-based filtering is direction-selective and whether cuing of the target direction promotes efficient search performance. In both experiments, the number of movement directions in a display and the predictability of the target direction were varied. Findings indicated that each was less efficient when items moved in multiple (two, three, and four) directions as compared with just one direction. In addition, it was found that precuing of the target direction facilitated the search, even with “wrap-around” displays, relatively more when items moved in multiple directions. In conclusion, interference on direction computation between items moving in different directions and selective direction tuning of motion detectors involving a receptive-field contraction are proposed as principles explaining this pattern of effects.